HOMOGENEOUS CHARGE COMPRESSION IGNITION IN A COMPRESSED NATURAL GAS ENGINE WITH A GASOLINE PILOT - NORAN, NORAZ AL-KHAIRI (2013)
Homogeneous Charge Compression Ignition (HCCI) is an autoignition combustion that is very promising in reducing the nitrogen oxides emissions. HCCI uses a very lean mixture that contributes to good fuel economy and produces high thermal efficiency. This is one of the solutions of the atmospheric air pollution and depleting fossil fuel resources. HCCIengines are still at the researchstage as there are no establish means for controlling the autoignition combustion. Under a very lean condition, the engine misfires while at high loads, often there will be an extremely loud and strong acoustic oscillations resembling knocking. This project proposed a method to control the HCCI combustion by direct injection of a secondary fuel, A homogeneous chargeof gasoline is injected in the inlet port and CNGdirect injection flow rates and degrees of stratification were identified as the potential parameters for HCCI combustion control.